Les sanctuaires du Djebel Nefousa - Basset, René (Journal asiatique, 1899)
Text and translation of Shammākhī: Siyar, 598-600. Pp. 434-436, Arabic text. Each of the 97 translated items is enriched with many elaborate annotations and references. On pp. 427-433 Basset gives a chronological survey of governors and dynasties in Ifrīqiyā, parallel to Imams and governors of Nafūsa and Imams of Tāhert.
Keywords: Prosopographie -- Djebel Nefousa

Etude sur la Zenatia du Mzab de Ouargla et de l'Oued-Rir' - Basset, René (Leroux, 1892)
Keywords: Linguistique

Loqmân berbère : texte et transcription, avec quatre glossaires et une étude sur la légende de Loqmân - Basset, René (Leroux, 1890)
Keywords: Linguistique

Les sanctuaires du Djebel Nefousa - Basset, René (Journal asiatique, 1899)
Text and translation of Shammākhī: Siyar, 598-600. Pp. 434-436, Arabic text. Each of the 97 translated items is enriched with many elaborate annotations and references. On pp. 427-433 Basset gives a chronological survey of governors and dynasties in Ifrīqiyā, parallel to Imams and governors of Nafūsa and Imams of Tāhert.
Keywords: Prosopographie -- Djebel Nefousa

Review: Chansons berbères de Djerba - Basset, René (Revue des traditions populaires, 1898)
Keywords: Recension